2020
DOI: 10.1128/mcb.00364-19
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Triggers Liver X Receptor-Dependent Lipogenesis

Abstract: Immune cell function can be modulated by changes in lipid metabolism. Our studies indicate that cholesterol and fatty acid synthesis increases in macrophages between 12 and 18 h after the activation of Toll-like receptors with proinflammatory stimuli and that the upregulation of lipogenesis may contribute to the resolution of inflammation. The inflammation-dependent increase in lipogenesis requires the induction of the liver X receptors, members of the nuclear receptor superfamily of transcription factors, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 76 publications
2
23
0
Order By: Relevance
“…10e ). While this inhibits their cholesterol synthesizing machinery by feedback control 37 , the pro-inflammatory milieu promotes cholesterol synthesis 38 . Indeed, we observed upregulated transcripts of sterol synthesizing enzymes apart from Dhcr24 mRNA, encoding the last enzyme of cholesterol biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…10e ). While this inhibits their cholesterol synthesizing machinery by feedback control 37 , the pro-inflammatory milieu promotes cholesterol synthesis 38 . Indeed, we observed upregulated transcripts of sterol synthesizing enzymes apart from Dhcr24 mRNA, encoding the last enzyme of cholesterol biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of SREBP expression is thus a likely explanation for the reduction in both fat accumulation in the liver and cholesterol and triglycerides levels in serum observed in the HFD+Vinegar_Bc mice. Additionally, activation of LXR has also been described to have anti-inflammatory effects in steatosis [55,56]. Therefore, the reduction in LXR expression could reflect the effect of vinegar and B. coagulans on systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of lipid metabolism via these transcription factors is important for short term immune cell activation as well as long-term trained innate immunity 58,[71][72][73][74] . However, loss of function experiments indicated that LXRs and SREBPs were not required for the antiinflammatory effects of 3'SL on LPS treated macrophages.…”
Section: Discussionmentioning
confidence: 99%